2019
DOI: 10.3389/fonc.2019.01430
|View full text |Cite|
|
Sign up to set email alerts
|

Isothermal Microcalorimetry of Tumor Cells: Enhanced Thermogenesis by Metastatic Cells

Abstract: Tumor cells exhibit rewired metabolism. We carried out comparative analyses attempting to investigate whether metabolic reprograming could be measured by isothermal microcalorimetry. Intact metastatic cell lines of tongue cell carcinoma, human and murine melanoma, lung, and breast tumors consistently released more heat than nonmetastatic cells or cells displaying lower metastatic potential. In tongue squamous carcinoma cells mitochondrial enriched extract reproduced the heat release pattern of intact cells. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Tumor cells for example exhibit a significantly different and elevated metabolism from that of other cells. Changes in lipid metabolism have been linked with changes of the thermogenic profile [ 12 ]. Thermogenesis can be measured by isothermal microcalorimetry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tumor cells for example exhibit a significantly different and elevated metabolism from that of other cells. Changes in lipid metabolism have been linked with changes of the thermogenic profile [ 12 ]. Thermogenesis can be measured by isothermal microcalorimetry.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that metastatic cells utilize metabolic pathways that supply extra energy to enable increased motility and invasiveness [ 12 ]. For example, Lemos et al described an increased heat release exclusively in metastatic cell lines of different origins (human oral squamous cell carcinoma, melanoma, non-small-cell lung and breast cancer, and murine melanoma cells) [ 12 ]. They investigated the influence of MAGEA10 protein on this process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations